A role for Kalirin-7 in corticostriatal synaptic dysfunction in Huntington's disease - Puigdellívol, Mar (Hum Mol Genet, 2015)
Cognitive dysfunction is an early clinical hallmark of Huntington's disease (HD) preceding the appearance of motor symptoms by several years. Neuronal dysfunction and altered corticostriatal connectivity have been postulated to be fundamental to explain these early disturbances. However, no treatments to attenuate cognitive changes have been successful: the reason may rely on the idea that the temporal sequence of pathological changes is as critical as the changes per se when new therapies are in development. To this aim, it becomes critical to use HD mouse models in which cognitive impairments appear prior to motor symptoms. In this study, we demonstrate procedural memory and motor learning deficits in two different HD mice and at ages preceding motor disturbances. These impairments are associated with altered corticostriatal long-term potentiation (LTP) and specific reduction of dendritic spine density and postsynaptic density (PSD)-95 and spinophilin-positive clusters in the cortex of HD mice. As a potential mechanism, we described an early decrease of Kalirin-7 (Kal7), a guanine-nucleotide exchange factor for Rho-like small GTPases critical to maintain excitatory synapse, in the cortex of HD mice. Supporting a role for Kal7 in HD synaptic deficits, exogenous expression of Kal7 restores the reduction of excitatory synapses in HD cortical cultures. Altogether, our results suggest that cortical dysfunction precedes striatal disturbances in HD and underlie early corticostriatal LTP and cognitive defects. Moreover, we identified diminished Kal7 as a key contributor to HD cortical alterations, placing Kal7 as a molecular target for future therapies aimed to restore corticostriatal function in HD.